2012
DOI: 10.2146/ajhp110723
|View full text |Cite
|
Sign up to set email alerts
|

Fall risk associated with inpatient medications

Abstract: In a sample of hospitalized patients, CNS agents were significantly associated with falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Fifty seven percent of the studies did not specify the medication, class or substances included in the group (only mentioned, for instance, sedative hypnotics, without indicating any specific drug) (Costa-Dias et al, 2014;Pierce Jr. et al, 2013;Obayashi et al, 2013;Lamis et al, 2012;Chang et al, 2011;Bun, Serby, Friedmann, 2011;Mamun, Lim, 2009;Tanaka et al, 2008;Angalakuditi, Gomes, Coley, 2007;Vassalo et al, 2006;Krauss et al, 2005;Vassalo et al, 2004;Aisen, Deluca, Lawlor, 1992). Some articles focused their studies on all central nervous system medications (Lamis et al, 2012) (without establishing any distinction between the pharmacological groups).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifty seven percent of the studies did not specify the medication, class or substances included in the group (only mentioned, for instance, sedative hypnotics, without indicating any specific drug) (Costa-Dias et al, 2014;Pierce Jr. et al, 2013;Obayashi et al, 2013;Lamis et al, 2012;Chang et al, 2011;Bun, Serby, Friedmann, 2011;Mamun, Lim, 2009;Tanaka et al, 2008;Angalakuditi, Gomes, Coley, 2007;Vassalo et al, 2006;Krauss et al, 2005;Vassalo et al, 2004;Aisen, Deluca, Lawlor, 1992). Some articles focused their studies on all central nervous system medications (Lamis et al, 2012) (without establishing any distinction between the pharmacological groups).…”
Section: Resultsmentioning
confidence: 99%
“…Some articles focused their studies on all central nervous system medications (Lamis et al, 2012) (without establishing any distinction between the pharmacological groups). Some studies grouped more than one pharmacological group (Costa-Dias et al, 2014;Vassalo et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of that case-control study showed strong positive associations at 0 days for all classes of medication (β-blockers, angiotensin-converting enzyme inhibitors, calcium antagonists, thiazides). Surprisingly, only thiazides showed significant ORs of falling during elapsed times of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] 16 A study showed that the current prescribing of angiotensin system-blocking medications, including angiotensin-converting enzyme inhibitors and angiotensinreceptor blockers, had a protective effect against fall risk in older people. 29 This prospective cohort study in 520 community-dwelling older people indicated that people taking angiotensin system-blocking medications were less likely to fall (OR 0.68, 95% CI 0.48-0.97; P,0.05) after adjusting for potential confounders.…”
mentioning
confidence: 99%